(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This article provides information on inaccessible ponds, basins and networks. There is also information about the water networks flowing across the borders of the world and the purposes and issues of international agreements, treaties, mutual agreements on it. In addition, there is talk of a positive development of relations between the Central Asian states on this issue.